M’sians increasingly aware of risks with data breach - Zulhuda, Sonny (2019)
Malaysians are increasingly more aware of the risks associated with breaches of their personal data, and we have seen a sharp increase in data privacy civil suits in the local Malaysian courts in the past five years, Straits Interactive says. When queried on the cost of data breaches in the Asean region, particularly in Malaysia, Straits Interactive senior consultant in Malaysia, Dr Sonny Zulhuda told The Borneo Post in an email interview that the cost of data breaches can be seen in many areas.